Spectrophotometric determination of magnesium oxide content in supplements of magnesium - Mandal, Šaćira (Array, 2019)
Magnesium is an essential element and the intracellular divalent cation involved in many biochemical functions. People with magnesium deficiency must increase their intake of magnesium, usually in the form of various supplements. A common form of magnesium supplement widely available in pharmacies is magnesium oxide (MgO). In this work, the content of MgO was determined in pharmaceutical supplementations using spectrophotometry, based on the reaction between magnesium ions and eriochrome black T at a wavelength of 535 nm. The analysed content of MgO ranged from 360.5 to 386.5 mg MgO, which corresponds to the daily Mg recommended values (300 to 400 mg).